Issue Information TOC. Issue 1 (20th June 2019) - Unknown
Abstract : Cover : In Zhao et al. (https://doi.org/10.1002/cpcy.55 ), Detection of histone H2AX phosphorylated on Ser‐139 (γH2AX) induced by topotecan (Tpt) or etoposide (Etp) in relation to cell position in the cell cycle. Bivariate cellular DNA content versus γH2AX Immunofluorescence (IF) distributions (scatterplots) are shown for TK6 cells left untreated (Ctrl) or treated in culture with 0.15 μM Tpt or 10 μM Etp for 2 hr, as previously described (Tanaka et al., 2007). See e55.